The pan-immune-inflammation value predicts prognosis and chemotherapy-related adverse events in Wilms’ tumor patients - Kongkong Cui; Jie Lin; Peng Hong; Honggang Fang; Zaihong Hu; Zhiqiang Gao; Xiaomao Tian; Qinlin Shi; Guanghui Wei (BMC Cancer)
Abstract Background Wilms’ tumor (WT) is a common renal malignancy in children. Although certain patient groups exhibit high survival rates, those experiencing recurrence, metastasis, or chemoresistance face significant challenges. The identification of reliable prognostic markers is essential for adapting treatment strategies to enhance survival rates and reduce chemotherapy-related adverse events (CRAEs). Methods This study included patients diagnosed with WT at our institution. Inflammatory biomarkers were measured from pre-treatment blood tests, and their associations with event-free survival (EFS) and overall survival (OS) were evaluated using Kaplan-Meier and Cox regression analyses. The relationship between biomarkers and CRAEs was examined through logistic regression. Results Multifactorial Cox regression analysis identified tumor stage (HR = 4.68, 95% CI: 1.58–13.87, p = 0.005), pan-immune-inflammation value (PIV) (HR = 3.94, 95% CI: 1.80–8.60, p < 0.001), and neutrophil-to-lymphocyte ratio (NLR) (HR = 0.40, 95% CI: 0.18–0.90, p = 0.027) as independent prognostic factors for EFS. Multivariate Cox regression revealed that stage IV (HR = 12.24, 95% CI: 1.56–95.85, p = 0.017) and PIV levels exceeding 246.4 (HR = 5.50, 95% CI: 2.13–14.19, p < 0.001) were significant predictors for OS. Additionally, high PIV (OR 2.32, 95% CI: 1.15–4.67, p = 0.018) independently predicted the occurrence of CRAEs. Conclusion WT patients with higher PIV levels showed significant associations with poorer EFS, worse OS, and an increased likelihood of developing CRAEs during treatment.